Prevalence and factors associated with institutional delivery in rural Afghanistan: secondary analysis of the 2022-2023 multiple indicator cluster survey - Stanikzai, Muhammad Haroon; Tawfiq, Essa; Jafari, Massoma; Golzareh, Parvin; Farooqi, Khushhal; Sayam, Hadia; Wasiq, Abdul Wahed; Dadras, Omid (BioMed Central, 2026)
Background: Institutional delivery rates among rural women appear to still be suboptimal, mainly in low and middle-income countries (LMICs). Despite that, there has been a lack of research addressing this issue among women in rural Afghanistan. Hence, this study aimed to assess the prevalence and factors associated with institutional delivery among women in rural Afghanistan.
Methods: In this cross-sectional study, we used the 2022–2023 Afghanistan Multiple Indicator Cluster Survey (MICS) for analysis. A total of 10,644 ever-married women, aged 15–49 years, who gave birth to a live baby in the past 2 years and lived in rural areas of Afghanistan were included in this analysis. The outcome was institutional delivery and was defined as a live birth delivered by an ever-married woman at a public or private health facility in the past 2 years prior to the MICS. We applied a binary logistic regression model and provided adjusted odds ratios (AORs) and 95% confidence intervals (CIs) on the factors associated with institutional delivery.
Results: Out of 10,644 women, 59.4% delivered at a health facility in their last pregnancy. We found that women in the age groups 30–39 years [AOR = 1.16, 95% CI (1.05–1.28)] and 40–49 years [1.28 (1.08–1.51)], women with formal education [1.56 (1.35–1.79)], women living in households with educated heads [1.19 (1.07–1.33)], women who had 1–3 antenatal care (ANC) visits [3.12 (2.81–3.47)] and ≥ 4 ANC visits [5.42 (4.78–6.15)], women who had access to mobile phones [1.26 (1.15–1.39)], women in the third [1.73 (1.51–1.98)], fourth [2.30 (1.98–2.66)], and highest [3.66 (3.05–4.39)] wealth households, and those with media access [1.24 (1.09–1.41)] were more likely to use institutional delivery. However, the likelihood was lower in multipara women [0.65 (0.57–0.74)].
Conclusion: Just more than half of Afghan women opt for institutional deliveries in rural settings. There is a pressing need for concerted efforts aimed at enhancing access to maternal healthcare services, taking into account the associated factors identified in this context.